Perceived Consequences of Late Diagnosis and Utilization of Cervical Cancer Screening among Gynecology Clinics Attendees in Ibadan, Nigeria (2019)
Background: Cervical Cancer (CC) is the second most common cancer in women after breast cancer in the developing countries. It has been reported that case fatality rate (CFR) of CC is high especially at the late and invasive stage. Available statistics shows that majority of women are unaware of CC nor utilized screening services as these have remained low in the developing world. Objectives: To evaluate the perceived consequences of late CC diagnosis and utilization of Cervical Cancer Screening Services (CCSS) among gynaecology clinic attendees in Ibadan, Nigeria. Methodology: This cross-sectional study was carried out among 138 women and undergoing treatment for gynaecological condition in a tertiary institution in Nigeria. They were selected through simple random sampling method. Data were collected using self-administered questionnaire after obtaining ethics approval and informed consent from the participants. Data was analysed using Stata statistical software for windows version 14; Chi-square test was used to determine associations between the variables with significant level of p<0.05. Results: Most respondents 78(56.5%) lacked understanding of consequences of late diagnosis of CC and only 27(19.6%) of the respondents had ever utilized CCSS. There is significant association between: perceived consequences and readiness to be screened for CC (-44.142, p<0.001); educational level and readiness to utilize CCSS (=18.125, p<0.006) as well as knowledge and readiness for CCSS (38.818, p<0.001). No significant association was found between perceived consequences of late diagnosis of CC and utilization of CCSS (=0.013, P=0.910) but educational level and utilization of CCSS has significant association (2=8.998, p=0.029). Conclusions: Since most women attending the gynaecological clinic have not utilized cervical cancer screening services and have poor perception about the consequences of late diagnosis. There is need for structured educational strategies to improve knowledge of consequences of not screening for cervical cancer.